Repositioning African Union Agenda 2063: An Exploration of the Nexus between People Centered Development and Indigenous Knowledge Systems (With Specific Reference to AU Aspiration 6) - ISIOMA UREGU ILE (African Journal of Governance and Development, 2020)
Agenda 2063 of the African union (AU) – the Africa we want” has been implemented for over five years now, however, there is a concern that if implementation is not done ‘intentionally’, by 2063, it would not have achieved the desired impact. Therefore, this paper attempts to present a clear approach as well as strategies that could contribute to the successful implementation of “Aspiration 6” (A6) in particular, one of the seven identified AU aspirations. This discourse is engaged in from the theoretical approach of Appreciative Inquiry (AI) which focuses on positive outcomes. Firstly, the paper explores Aspiration 6 on people centered development. With majority of Africa’s population made up of women, youth and children, this paper argues that these identified segments of the population should be put at the center of all developmental pursuits. The analysis undertaken, examined identified United Nations Sustainable Development Goals (SDGs) specifically 4 & 17, as enablers for the realization of A6. Secondly, this paper identifies points of convergence between these developmental goals and pre-existing indigenous knowledge systems (IKS). In doing so, it is posited that, from an African perspective, IKS presents an opportunity for the effective realization of the “Africa we want”. Lastly, strategies to deliberately support IKS through re-orienting research capacity and capabilities are presented. The paper concludes by making key recommendations.